Dynamic release of gentamicin sulfate (GS) from alginate dialdehyde (AD)-crosslinked casein (CAS) films for antimicrobial applications. Issue 1 (1st January 2017) - Bajpai, S. K.; Shah, Farhan Ferooz; Bajpai, M.
Abstract: In the present work, antibiotic drug gentamicin sulfate (GS) has been loaded into alginate dialdehyde-crosslinked casein (CAS) films for wound dressing applications. The films have been characterized by Fourier transform infrared spectroscopy, X-ray diffraction analysis and scanning electron microscopy. The dynamic release of model drug GS has been investigated in the physiological fluid at 37 °C. The drug release data has been interpreted in the terms of various kinetic models such as Power function model, first order model and Schott model. The release data was found to be well fitted by Schott model. The various diffusion coefficients are also evaluated. The adsorption of model therapeutic protein BSA on the film has been investigated. The maximum adsorption is found to be 5.7 mg/cm 2 .The films were tested for their antibacterial and anti-fungal action. Finally, the in vivo wound healing study was carried out on Albino wistar rats.